The Salem world of Nathaniel Hawthorne - Moore, Margaret B. (Univ. of Missouri Press, 1998)
Although most writers on Nathaniel Hawthorne touch on the importance of the town of Salem, Massachusetts, to his life and career, no detailed study has been published on the background bequeathed to him by his ancestors and present to him during his life in that town. The Salem World of Nathaniel Hawthorne examines Salem's past and the role of Hawthorne's ancestors in two of the town's great events - the coming of the Quakers in the 1660s and the witchcraft delusion of 1692. Margaret B. Moore thoroughly investigates Hawthorne's family, his education before college (about which almost nothing has been known), and Salem's religious and political influences on him. She details what Salem had to offer Hawthorne in the way of entertainment and stimulation, discusses his friends and acquaintances, and examines the role of women influential in his life - particularly Mary Crowninshield Silsbee and Sophia Peabody. Nathaniel Hawthorne felt a strong attachment to Salem. No matter what he wrote about the town, it was the locale for many of his stories, sketches, a novel, and a fragmentary novel. Salem history haunted him, and Salem people fascinated him. And Salem seems to have a perennial fascination for readers, not just for Hawthorne scholars. New information from primary sources, including letters (many unpublished), diaries, and contemporary newspapers, adds much not previously known about Salem in the early nineteenth century.